The determinants of food insecurity among developing countries: Are there any differences? - Atif Awad (Scientific African, 2023)
It has been widely recognized that certain socioeconomic factors play a crucial role in explaining food insecurity in a country or region. Yet, while the evidence continues to indicate substantial discrepancies in food insecurity across developing economies, no empirical study has attempted to determine the causes of these discrepancies. This study aimed to identify the leading causes of food insecurity in 107 developing countries spread across three separate continents between 2000 and 2019. The study employed recent techniques in data analysis that deal with heterogeneous panel methods robust to cross-sectional dependence. The panel-corrected standard error (PCSE) technique, which was used in the analysis, showed that disparities in food insecurity were not due to population growth, health services, or food production, since they had similar effects in all of the developing economies in Africa, Asia and the Latin America and the Caribbean region. However, political institutions, per capita income, and education were vital factors that explained the observed disparities in malnutrition between them.